The politics of surviving: how women navigate domestic violence and its aftermath - Sweet, Paige L. (University of California Press, 2021)
Introduction : Domestic violence and the politics of trauma -- Building a therapeutic movement -- The trauma revolution -- Administering trauma -- Becoming legible -- Gaslighting -- Surviving heterosexuality -- Conclusion : Traumatic citizenship.